If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 4)(3x + -3) = 0 Reorder the terms: (4 + 5x)(3x + -3) = 0 Reorder the terms: (4 + 5x)(-3 + 3x) = 0 Multiply (4 + 5x) * (-3 + 3x) (4(-3 + 3x) + 5x * (-3 + 3x)) = 0 ((-3 * 4 + 3x * 4) + 5x * (-3 + 3x)) = 0 ((-12 + 12x) + 5x * (-3 + 3x)) = 0 (-12 + 12x + (-3 * 5x + 3x * 5x)) = 0 (-12 + 12x + (-15x + 15x2)) = 0 Combine like terms: 12x + -15x = -3x (-12 + -3x + 15x2) = 0 Solving -12 + -3x + 15x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-4 + -1x + 5x2) = 0 Factor a trinomial. 3((-4 + -5x)(1 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-4 + -5x)' equal to zero and attempt to solve: Simplifying -4 + -5x = 0 Solving -4 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -5x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = 0 + 4 -5x = 0 + 4 Combine like terms: 0 + 4 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-0.8, 1}
| x-8=4x | | 9x^2=51x-60 | | 6(t-5)+8t=7(2t+4)-11 | | 5t+2+4t-8t=5+5 | | 4(x-3)=-(x+7) | | (x-5)(x+3)(x+4)=0 | | x-(x+1)=12-(3x-2) | | y=x^2-x-23 | | 4(9v+2)=6(1+6v)-10 | | 2x=x+65 | | -2(c-d)+(c-3d)-5(c-d)= | | -0.5x^2+2x-70=0 | | 6a+4=a+7 | | -20x^2-8x+64=0 | | 2n^2+33n-17=0 | | 2.5x+0.25x=0.75+x | | 4x+9=3x+5 | | 6m^2=23m-15 | | 0.36(18)+0.04x=0.12(6+x) | | -2x+3y-5x-(-8y)+9y= | | 4+2x*6=x*-10+2 | | 9x^2=33x-30 | | 8x=3x-45 | | 4m^2-12m+9=0 | | -7-3y=8 | | 201-2x=43+16 | | 8x-51=3x | | 5-4y+x+9y= | | 4x+13=-7-9x | | 155-6x=4x | | 4(x+5y)+(5x+y)= | | 1.23x+0.125x=0.375+x |